2022
DOI: 10.1038/s41385-022-00545-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct airway epithelial immune responses after infection with SARS-CoV-2 compared to H1N1

Abstract: Children are less likely than adults to suffer severe symptoms when infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), while influenza A H1N1 severity is comparable across ages except for the very young or elderly. Airway epithelial cells play a vital role in the early defence against viruses via their barrier and immune functions. We investigated viral replication and immune responses in SARS-CoV-2-infected bronchial epithelial cells from healthy paediatric (n = 6; 2.5–5.6 years old) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…Many studies to date have investigated differences in transcriptional responses to IAV and SCV2, a subset of which are cited here [ 31 , 32 , 62 , 63 ]. However, a majority of studies have focused on easily accessible patient blood samples for biomarker discovery or have taken samples from deceased patients, which represent late infection timepoints and heterologous cellular samples from which it is more difficult to draw specific mechanistic conclusions [ 16 , 17 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies to date have investigated differences in transcriptional responses to IAV and SCV2, a subset of which are cited here [ 31 , 32 , 62 , 63 ]. However, a majority of studies have focused on easily accessible patient blood samples for biomarker discovery or have taken samples from deceased patients, which represent late infection timepoints and heterologous cellular samples from which it is more difficult to draw specific mechanistic conclusions [ 16 , 17 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, responses to infection have been shown to be cell specific; therefore, great care must be taken about the context of the conclusions drawn from these types of studies [ 29 ]. Even within respiratory epithelial cells, it is important to distinguish between cultures derived from the upper and lower respiratory tract when designing these studies, as there are important differences in cell type proportion and receptor expression in addition to specific microenvironments [ 18 , 19 , 20 ] Other groups have reported an attenuated response to early SCV2 infection, especially in nasal epithelial cells, with most responses not being observed until 72 HPI [ 31 , 32 ]. This study has important limitations, namely the use of a single donor for the RNA-sequencing samples to limit variability in order to focus on specific virus- and temperature-related responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic T lymphocytes (CTLs) or Natural Killer (NK) cells kill infected epithelial cells by inducing apoptosis [ 9 ]. Alternatively, IAV-infected epithelial cells can undergo PCD, even in monoculture [ 10 ], by activating apoptotic, necroptotic or pyroptotic pathways, as recently reviewed by Laghlali et al [ 8 ]. These PCD modalities are antiviral, as IAV-induced cell death limits viral dissemination rather than supporting new virion release [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This unregulated inflammation leads to lung injury, which has been shown to persist for up to 2 months in mice 21 . Additionally, multiple studies have shown that both SARS-CoV-2 and IAV infection of human airway epithelial cell cultures induce IP10 signaling and interferon responses, but that the overall inflammatory response is attenuated in SARS-CoV-2 infected cultures as compared to IAV infected cultures 26, 67 .…”
Section: Introductionmentioning
confidence: 99%